PRELIMINARY DETERMINATION OF ESSENTIAL AND TOXIC ELEMENTS IN BUCKWHEAT (Fagopyrum esculentum) BY INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY - Monica Perez; Matias Riffo; Maria Luisa Valenzuela; Carlos G Peña-Farfal (Journal of the Chilean Chemical Society, 2023)
This paper describes the preliminary determination of some element concentration in buckwheat and commercial buckwheat flour determined by ICP-MS. The results indicate how essential and toxic elements added in the soil were absorbed by the buckwheat seeds planted and how the elements concentration of the new seeds was affected by this intentional addition. Results showed limits of detection and quantification range from 0.008 to 1.085 µg/Kg. Correlation coefficients (r) were calculated in the range of 0.9920 to 0.9999. The data obtained described that some elements are far below LOD and LOQ in µg/Kg concentrations in the grains. and that ICP-MS was a very precise method to determinate simultaneously many elements at the same time.